Translation and the Application of Linguistics - Dasgupta, Probal (Meta, 1994)
Abstract This article explores some topics at the boundary between linguistics theory and the applied linguistic foundations of the practice of translation. Section 1, The irrelevance of the avant-garde , considers the relation between such academic adventures as semiotics and poststructuralism on the one hand and the theory of language and the practice of translation on the other, and argues that radical antiscientism does not bear on the foundations of translation. Section 2, The irrelevance of the technical , looks at formal syntax and semantics in relation to the concepts of applied linguistics and shows that careful contemporary linguistics cannot underpin an applied enterprise that includes translation studies. Section 3, The substantive hase of translation , indicates (in some detail for translation and at a general level for other applied linguistic activities) the direction that the contemporary integration of various lines of linguistic research is taking vis-à-vis the needs of such applied enterprises as translation, literary studies, language planning, lexicography, and language teaching. Section 3 invokes a concept of substance as opposed to form and thus sets the scene for the concluding section 4, Pragmatics, applied studies, and scientific progress , which argues that it is necessary to take help from linguistics in order to construct the field of translation studies in such a way that practitioners can truly benefit freely from all relevant branches of knowledge, in view of the fact that chaos is an obstacle to genuine freedom.